MESOTERAPI (MESOLIPOLYSIS INJECTION) PERSPEKTIF HUKUM ISLAM - Asmarini, Andini (Program Studi Perbandingan Mazhab, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2023)
Someone's appearance has become crucial in today's world due to various factors, including work and lifestyle. Mesotherapy is one type of facial and body treatment that is widely used today. Mesotherapy, also known as mesolipolysis injection technique, was initially developed for the treatment of diseases but is now widely employed for cellulite treatment, lipolysis or body contouring, and other cosmetic treatments. While beauty and aesthetics are encouraged, Islam provides guidelines for regulating them. Mesotherapy is permissible when done for the purpose of treatment, maintaining health, self-care as a form of gratitude to Allah, intending to look beautiful in front of one's husband, using permissible and non-impure substances, and without altering Allah's creation. However, mesotherapy becomes prohibited if it involves impure or forbidden elements, poses a health risk, or is intended to display beauty to non-mahram men.